Synthesis of hierarchical wo3 microspheres for photoelectrochemical water splitting application - Aiymkul Markhabayeva; R. Dupre; R. Nemkayeva; N. Nuraje (Physical Sciences and Technology, 2023)
In this work, hierarchical WO3 microspheres were synthesized using chemical bath deposition. The morphology of the synthesized sample was studied using scanning electron microscopy (SEM). The hierarchical WO3 microspheres formed from spontaneously self-assembled nanosheets have a high specific surface area.